Pursuing innovative actions during Covid-19 crisis: a qualitative analysis of family firms’ resilience - Cucino, Valentina; Ferrigno, Giulio; Piccaluga, Andrea (Piccola Impresa / Small Business, 2023)
Purpose: The study aims to broaden and refine the extant theory in the area of resilience in family firms during a grand challenge such as Covid-19. More specifically, the study aims to explore how characteristics that normally contribute to the resilience of family businesses also influence their innovative actions when facing a grand challenge Design/methodology/approach. This study reviews what has been written on resilience in family firms and their innovative actions in the exceptional context of Covid-19. Then, through an inductive approach based on multiple case studies, qualitative data (primary and secondary sources of information) collected from five Italian family businesses that have demonstrated success in responding to Covid-19 are triangulated. Findings. The findings seem to reveal that, during Covid-19, some features that normally contribute to the resilience of family firms (i.e. trust, long-term orientation, centralized and personalized authority structures, and patient capital) also contribute to their resilience, through innovative actions, to react to the Covid-19 grand challenge. Originality of the study. The study reveals that a further element (namely purpose driven orientation) not previously discussed in family business literature allowed the firms analyzed to be resilient during the Covid-19. Drawing on these findings, our paper aims to enrich the current understanding of family firms’ resilience for both academics and managers.